Addressing special educational needs and disability in the curriculum maths - Wallace, Max (Mathematics teacher) (New York Routledge, 2018)
"The SEND Code of Practice (2015) reinforced the requirement that all teachers must meet the needs of all learners. This topical book provides practical, tried and tested strategies and resources that will support teachers in making maths lessons accessible and interesting for all pupils, including those with special needs. The author draws on a wealth of experience to share his understanding of special educational needs and disabilities and show how the maths teacher can reduce or remove any barriers to learning."--Provided by publisher.
Introduction -- Meeting SEND : your responsibility -- The inclusive mathematics classroom -- Teaching and learning -- Monitoring and assessment -- Managing support and intervention -- Real pupils in real classrooms.
Includes bibliographical references.
Keywords: Mathematics -- Study and teaching -- Great Britain; Special education -- Great Britain; Children with disabilities -- Education -- Great Britain